Papel do receptor NOD2 na patogenia das lesões do sistema digestivo da doença de Chagas - Nathalie de Sena Pereira (2018)
Digestive and cardiodigestive forms of Chagas' disease are observed in 2% to 15% of the patients, but immunopathological mechanisms remain undefined. Although studies have demonstrated the importance of inflammation and the presence of the parasite in the esophagus and colon in the pathophysiological process of megacolon and megaesophagus generation in chronic chagasic patients. The mechanism by which some patients develop these anatomopathological alterations is unclear. The NOD2 molecule is an innate immune receptor, expressed mainly in macrophages and dendritic cells. The NOD2 receptor is also highly expressed in Paneth cells and maintains intestinal homeostasis, prevents the penetration of bacteria into the epithelium of the gastrointestinal tract. This work aimed to evaluate the role of the NOD2 receptor (Nucleotide-Binding Oligomerization Domain 2) in the pathogenesis of the digestive system in Chagas' disease. The expression of NOD2, RIP2 (Receptor-interacting protein kinase 2) and defensins 5 and 6 was evaluated in peripheral blood mononuclear cells of patients with the indeterminate (n = 18), cardiac (n = 17), digestive (n = 15) and cardiodigestive (n = 15) of Chagas disease, using real-time PCR, correlated with the degree of dilation of the esophagus, sigmoid colon and rectum. Patients with the digestive and cardiodigestive forms of the disease had absent or reduced expression of NOD2 and high expression of RIP2 and defensin 6 when compared with those with indeterminate and cardiac forms. The negative correlation between the expression of NOD2 mRNA with the degree of esophageal dilation and the size of the sigmoid and rectum was also observed. Subsequently C57BL/6 and NOD2-/- mice were infected with 1 × 103 blood trypomastigotes of the isolated RN25 (obtained from patient with the digestive form) and evaluated the susceptibility to infection (parasitemia and mortality) and alterations of the gastrointestinal tract (motility, inflammation and denervation). NOD2-/- mice showed higher parasitemia from the 17th to the 30th day after infection when compared to C57BL/6 animals. In addition, NOD2-/- deficient females had reduced intestinal motility 15 and 180 days after infection when compared to C57BL/6 animals. Histopathological examination of the colon of NOD2-/- and female C57BL/6 animals demonstrated discrete inflammatory foci during the acute phase of infection (19 days post infection). During the chronic phase of the infection (12 months) there was inflammation and hypertrophy of the muscular layer in the colon and jejunum of the NOD2-/- animals, changes not observed in the C57BL/6 mice. Next, we raised the inoculum of T. cruzi to the mice was increased in order to promote the increase of the genesis of lesions of the gastrointestinal tract. Due to the low virulence of the RN25 isolate, female C57BL/6 and NOD2-/- mice were infected with 5 × 104 trypomastigotes of T. cruzi CL strain and infection susceptibility (parasitemia and mortality), gastrointestinal tract (TLR2, TLR4), transcription factor Th1 (T-bet), cytokines (IL-10, IL-17, TNF-, IFN-) and the expression of innate immunity receptors (TLR2, TLR4) ) and other inflammatory mediators (iNOS and defensin A) in the colon.. NOD2-/- animals present higher parasitemia between 30 and 60 days post infection, reduction of intestinal motility during the acute phase of infection and lower survival (60%) when compared to C57BL/6 animals (100% survival). Knockout mice of infected NOD2 showed increased expression of most of the inflammatory mediators analyzed in the acute phase (15 days post infection) when compared to wild animals. However, during the chronic phase (60 days after infection) the expression of inflammatory mediators in the gastrointestinal tract of NOD2 and C57BL/6 knockout animals infected with the CL strain was observed, similar to that of uninfected mice. Thus, deficient expression of NOD2 in patients with the digestive form of Chagas' disease and the increase of lesions with decreased motility of the gastrointestinal tract in experimentally infected NOD2-/- mice by T. cruzi isolate RN25 indicate that the absence or low NOD2 mRNA expression may be correlated with the development of the digestive form of Chagas' disease. Associated with the genetic profile of the parasite that generates persistent and discrete infection in several sites of the gastrointestinal tract, which when added can reach the critical level of myenteric plexus denervation leading to hyperexcitability, incoordination of peristaltic movements and hypertrophy.